An asymptotic expansion for a ratio of products of gamma functions - Wolfgang Bühring (International Journal of Mathematics and Mathematical Sciences)
An asymptotic expansion of a ratio of products of gamma functions is derived. It generalizes a formula which was stated by Dingle, first proved by Paris, and recently reconsidered by Olver